Clinical experience of using formoterol/budesonide in patients with chronic obstructive pulmonary disease - I. V. Demko; M. G. Mamaeva; E. A. Sobko; A. Yu. Kraposhina; N. V. Gordeeva (Медицинский совет, 2021)
Chronic obstructive pulmonary disease (COPD) today remains one of the most important problems of modern medicine. The social significance of this disease is determined by the annual health care costs for treating patients with exacerbated COPD, as well as the still high mortality and disability rates worldwide. The main goals of COPD treatment are to slow the rate of disease progression, control the symptoms, reduce the frequency of exacerbations and hospitalizations, and reduce the risk of future exacerbations. Currently, the main groups of drugs for basic therapy of COPD are inhaled prolonged bronchodilators from the groups of β2-adrenergic agonists and M-anticholinergics, as well as their combinations. Patients with COPD and bronchial asthma, as well as patients with COPD with elevated levels of eosinophils and frequent exacerbations, inhaled glucocorticosteroids (ICS) are used. It has been proven that the addition of corticosteroids to LABA in patients with moderate to severe COPD and frequent exacerbations has a more effective influence on pulmonary function and the number of exacerbations. Clinical studies have shown the relationship between the level of blood eosinophilia and the clinical effects of preventing future exacerbations when using iCS in combination with LABA. In our clinical observation, in patient with moderate COPD and blood eosinophilia > 300 cells/μL, when prescribing monotherapy with long-acting agonists, frequent exacerbations of the disease were noted. The addition of corticosteroids to monotherapy with a long-acting agonist made it possible to influence the frequency of exacerbations and reduce the level of eosinophils in the blood.